Global patterns of cardia and non-cardia gastric cancer incidence in 2012. Issue 12 (6th March 2015) - Colquhoun, A; Arnold, M; Ferlay, J; Goodman, K J; Forman, D; Soerjomataram, I
Abstract : Objective: Globally, gastric cancer incidence shows remarkable international variation and demonstrates distinct characteristics by the two major topographical subsites, cardia (CGC) and non-cardia (NCGC). Because global incidence estimates by subsite are lacking, we aimed to describe the worldwide incidence patterns of CGC and NCGC separately. Design: Using Cancer Incidence in Five Continents Volume X (CI5X), we ascertained the proportions of CGC and NCGC by country, sex and age group (<65 and ≥65 years). These derived proportions were applied to GLOBOCAN 2012 data to estimate country-specific age-standardised CGC and NCGC incidence rates (ASR). Regional proportions were used to estimate rates for countries not included in CI5X. Results: According to our estimates, in 2012, there were 260 000 cases of CGC (ASR 3.3 per 100 000) and 691 000 cases of NCGC (ASR 8.8) worldwide. The highest regional rates of both gastric cancer subsites were in Eastern/Southeastern Asia (in men, ASRs: 8.7 and 21.7 for CGC and NCGC, respectively). In most countries NCGC occurred more frequently than CGC with an average ratio of 2:1; however, in some populations where NCGC incidence rates were lower than the global average, CGC rates were similar or higher than NCGC rates. Men had higher rates than women for both subsites but particularly for CGC (male-to-female ratio 3:1). Conclusions: This study has, for the first time, quantified global incidence patterns of CGC and NCGC providing new insights into the global burden of these cancers. Country-specific estimates are provided; however, these should be interpreted with caution. This work will support future investigations across populations.